Stereoselective amine-thiourea-catalysed sulfa-Michael/nitroaldol cascade approach to 3,4,5-substituted tetrahydrothiophenes bearing a quaternary stereocenter - Meninno, Sara (Beilstein J Org Chem, 2016)
An investigation on the stereoselective cascade sulfa-Michael/aldol reaction of nitroalkenes and commercially available 1,4-dithiane-2,5-diol to 3,4,5-substituted tetrahydrothiophenes, bearing a quaternary stereocenter, is presented. A secondary amine thiourea derived from (R,R)-1,2-diphenylethylamine was found to be the most effective catalyst when using trans-β-methyl-β-nitrostyrenes affording the heterocyclic products in good yields and moderate stereoselectivities.